Reprogramming triggers endogenous L1 and Alu retrotransposition in human induced pluripotent stem cells - Jung-Klawitter, Sabine; Fuchs, Nina V.; Upton, Kyle R.; Muñoz-Lopez, Martin; Shukla, Ruchi; Wang, Jichang; Garcia-Cañadas, Marta; Lopez-Ruiz, Cesar; Gerhardt, Daniel J.; Sebe, Attila; Grabundzija, Ivana; Merkert, Sylvia; et al. (Nature Communications, 2016)
Genetic and epigenetic abnormalities have been found to result from reprogramming of differentiated cells into human induced pluripotent stem cells (hiPSCs). Here, Klawitter et al.identify endogenous L1, Alu and SVA mobilization during reprogramming, highlighting the risk of insertional mutagens in hiPSCs.
Gesehen am 13.04.2020